Word Formation Analysis of Foreign Terms in Information and Communication Technology Based on General Guidelines of Formation Terms in Indonesia - Nur Fitria, Tira (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
This research analyzes foreign terms in Information and Communication Technology (ICT) based on general guidelines for the Indonesian formation of terms (Pedoman Umum Pembentukan Istilah or PUPI). This research is descriptive qualitative. The analysis shows that Based on the General Guidelines for the Formation of Terms, the process of absorbing foreign terms in ICT into Indonesian can be classified into four processes, namely complete absorption, absorption through translation, absorption through adjustment of the form of writing, also absorption through adjustments to the form of writing and translation at the same time. While, the translation process by adjusting the form of writing is grouped into three forms of adjustment, namely spelling adjustment, adjustment of foreign consonant groups, and adjustment of foreign prefixes. In forming Indonesian computer terms, a collection of benchmarks and suggestions in General Guidelines for Enhanced Indonesian Spelling and General Guidelines. The emergence of ICT terms due to the advancement of science and technology can encourage Indonesians to adopt and form Indonesianized terms. Given the importance of the role of foreign terms in ICT as a ‘vehicle’ for the implementation of globalized international communication, ease of speed of mutual understanding between nations receives special attention from Indonesian computer terminology.